The intersection of trauma and eating disorders: evaluating cognitive processing therapy through qualitative analysis. - Suro, Giulia; Gavidia, Ismael; Tyran, Natalie; Perlman, Molly M.; Brewerton, Timothy D. (Eating Disorders)
Quantitative research has demonstrated that many individuals with eating disorders (EDs) present with PTSD (ED-PTSD). Cognitive processing therapy (CPT) has been integrated into the overall treatment for ED-PTSD, but qualitative data on the effectiveness of this approach is lacking. Ten patients with ED-PTSD completed 12 sessions of CPT during residential treatment (RT). After sessions 1 and 11, patients wrote an "impact statement" clarifying their beliefs about why their trauma occurred and how it has impacted their life. Two coders using MAXQDA2020 software evaluated these statements using a structured coding protocol to assess changes in trauma-related cognitions over time. Analyses of these cognitive changes demonstrated shifts in the appraisal process regarding why trauma occurred from stances of self-blame to external fault. Exploratory analyses also indicated that perceptions of control and safety were associated with a greater frequency of reference to EDs and body image. Qualitative findings demonstrated that trauma-related cognitions became more realistic and adaptive following CPT as evidenced by a significant reduction in assimilated and overaccommodated cognitions, and an increase in accommodated cognitions. Last, there was a notable shift in perceived responsibility for trauma and improvements in control and safety in relation to EDs.